The strategy of storynomics and its application in teaching speaking for university students: A literature review - Prasetyo, Lery; Benu, Naniana Nimrod; Supartini, Ni Luh; Sulasmini, Ni Made Ayu (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The main objective is to explore how integrating storytelling principles with strategic communication techniques can enhance oral language proficiency in higher education contexts. A qualitative literature review was employed, analyzing theoretical frameworks, empirical research, and case studies related to storytelling, storynomics, and language teaching methodologies. The findings suggest that storynomics enhances speaking instruction by creating a dynamic and interactive learning environment. It helps students relate to content, organize thoughts, and express ideas fluently and coherently while promoting authentic language use and creativity. Effective methods for implementing storynomics in classrooms include personal storytelling, digital storytelling, and role-playing. Challenges such as teacher preparedness, varied student proficiency levels, and time constraints in curricula were identified. The paper underscores the need for further research on the long-term effects of storynomics on speaking proficiency and its adaptability to different cultural contexts. Addressing these gaps will provide a more comprehensive understanding of its application in language education. In conclusion, storynomics presents a promising approach for enhancing speaking skills in higher education by making learning more engaging, practical, and interactive, ultimately contributing to improved student outcomes in verbal communication.